2017
DOI: 10.1007/s10948-017-4139-9
|View full text |Cite|
|
Sign up to set email alerts
|

Magnetocaloric-Transport Properties Correlation in La0.8 Ca0.2MnO3-Doped Manganites

Abstract: This investigation is interested in studying the relation between magnetocaloric effect and transport properties i La 0.8 Ca 0.2 MnO 3 manganite compound. The value of the magnetocaloric effect has been determined from the calculation of magnetization as a function of temperature under different external magnetic fields. This study also provides an alternative method to determine the magnetocaloric properties such as magnetic entropy change and heat capacity change on the basis of M(T , H ) measurements. On th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 20 publications
0
25
1
Order By: Relevance
“…We have estimated the Curie temperatures, of the samples from the inflection point of dM/dT versus plots and are shown in the insets. The pristine sample exhibits T C value of about 197 K which is much less than that reported for similar compound by Skini et al [12]. We can explain the reason for this variation in T C values.…”
Section: Magnetic Measurementcontrasting
confidence: 56%
See 1 more Smart Citation
“…We have estimated the Curie temperatures, of the samples from the inflection point of dM/dT versus plots and are shown in the insets. The pristine sample exhibits T C value of about 197 K which is much less than that reported for similar compound by Skini et al [12]. We can explain the reason for this variation in T C values.…”
Section: Magnetic Measurementcontrasting
confidence: 56%
“…In particular La 1-x Ca x MnO 3 (LCMO) compounds have attracted extra attention because of occurrence of enormous magneto-resistance (MR) and huge magneto-caloric effect (MCE) which makes them good candidates for applications [5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Rostamnejadi et al [10] have shown that La 0.67 Sr 0.33 MnO 3 manganites are ideal candidates for magnetic refrigeration above room temperature at moderate magnetic fields. In particular, La 1Àx Ca x MnO 3 compounds are important as they have the largest CMR effect, attributed to the presence of an electronic phase separation between hole-poor anti-ferromagnetic regions and hole-rich ferromagnetic regions [11][12][13][14]. Skini et al [13] has shown that lanthanum deficient manganites have MCE and RCP values close to gadolinium.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, La 1Àx Ca x MnO 3 compounds are important as they have the largest CMR effect, attributed to the presence of an electronic phase separation between hole-poor anti-ferromagnetic regions and hole-rich ferromagnetic regions [11][12][13][14]. Skini et al [13] has shown that lanthanum deficient manganites have MCE and RCP values close to gadolinium. Lee et al [14] have demonstrated that sintering temperature plays an important role on MCE and RCP.…”
Section: Introductionmentioning
confidence: 99%
“…(1) and (2), the entropy changes determined by the resistivity measurement and the Maxwell relation, described in our previous research work [7], are shown in Fig. 3.…”
Section: Resultsmentioning
confidence: 82%